(3EjVGM GdOdGdGJ aj SeGY GdBdGJs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM dYHGOg GdCMcGe CeG HYO ajbhd YHO GdZfi GdfGHdSi deG QCjfG GdfGS CcKQhG GdcdGe Hjf GdNhGU efge hGdYhGe ai eSFdI SeGY GdBdGJ HGdfZeGJ GdeWQjGJ acJHJ gPg GdQSGdI dCgd GdEfUGa ef GdENhGf s
(3BNQgG (B:s
(3hef CfcQ GdSeGY ef GdeJbOejf hef GdeJCNQjf EfeG eQGOge GdbSe GdaGSO ef Pdc hdG NdGa ai Ojf Gddg JYGdi ai gPg GdeSFdI Hjf YdeGA gPg GdedI GdESdGejI hGddg GdgGOi Edi ShGA GdSHjd hGddg MSHfG hfYe Gdhcjd fYe Gdehdi hfYe GdfUjQ s
(3HgG fXGe GdJYbjHIs
(3HChdgG hBNQgG fbhd TYQjI eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B154s
Keywords: (3Gdabg GdESdGejs